2022
DOI: 10.1136/bmjsem-2021-001225
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-Strengthening Exercise Questionnaire (MSEQ): an assessment of concurrent validity and test–retest reliability

Abstract: ObjectivesMuscle-strengthening exercise (MSE) has multiple independent health benefits and is a component of global physical activity guidelines. However, the assessment of MSE in health surveillance is often limited to the constructs of frequency (days/week), with little focus on constructs such as MSE type, muscle groups targeted and intensity. This study describes the test–retest reliability and concurrent validity of the Muscle-Strengthening Exercise Questionnaire (MSEQ), which was developed to assess mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In our study, assessing MSE was based on one single question, which only focused on frequency of MSE per week owing to the standardised measurement protocol of the YRBS. It is recently recognised that assessing MSE at the population level should consider more components, such as duration, type and intensity [ 31 , 32 ]. Such data, however, is lacking in our study but it is urgently needed to address this research issue for better capturing information on MSE in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, assessing MSE was based on one single question, which only focused on frequency of MSE per week owing to the standardised measurement protocol of the YRBS. It is recently recognised that assessing MSE at the population level should consider more components, such as duration, type and intensity [ 31 , 32 ]. Such data, however, is lacking in our study but it is urgently needed to address this research issue for better capturing information on MSE in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the original version, the MSEQ Indonesian version had higher test–retest reliability (ICC range from 0.51 to 0.96 and from 0.54 to 0.97, respectively) and concurrent validity (ρ range from 0.30 to 0.77 and from 0.73 to 0.82, respectively) in assessing the frequency, duration, and intensity of overall MSE [10] . This finding indicated that the addition of definition and explanation questions enhanced the comprehension of the MSEQ Indonesian version and consequently its reliability and validity [32] .…”
Section: Discussionmentioning
confidence: 99%
“…The Muscle-Strengthening Exercise Questionnaire (MSEQ) is a valid and reliable instrument designed to assess MSE in an online, self-report format developed for the adult population [10] . The items assessed include the following dimensions: 1) frequency, 2) intensity, 3) duration, 4) type of exercise, and 5) targeted muscle groups of MSE [11] .…”
Section: Introductionmentioning
confidence: 99%
“… 51 We will assess the following determinants: culture, acceptability, feasibility, adaptability, compatibility (appropriateness), dose (satisfaction), capability, opportunity and motivation using a teacher survey (~20 min). This survey has not been used previously; however, it is based on a body of literature per different implementation outcomes including (n=number of survey items): participation in muscle strengthening exercise (6) 52 culture (1), 53 acceptability (1), feasibility (1), compatibility (appropriateness) (1), 54 adaptability (3), dose (satisfaction) (2), 55 capability (4), opportunity (5) and motivation (4). 56 All school champions will complete the questionnaire and will advise other teachers delivering the programme within their school to do the same.…”
Section: Methodsmentioning
confidence: 99%